Pengaruh Kualitas Pelayanan Kesehatan Terhadap Kepuasan Pasien Di Puskesmas Pangkajene Kecamatan Maritenggae Kabupaten Sidenreng Rappang - Shofiyah, Ari fatus; Lukman, Lukman; Uceng, Andi; Sinrang, Andi (Saraq Opat: Jurnal Administrasi Publik, 2025)
The purpose of this study is to determine the influence of the quality of health services on patient satisfaction at the Puskesmas Pangkajene, Maritenggae District, Sidenreng Rappang Regency. This research uses a quantitative descriptive approach. The population in this study consisted of patients who received treatment at the Puskesmas Pangkajene, totaling 125. The sample in this study was 55 respondents determined using Slovin's formula and random sampling technique. The data collection techniques used in this study were observation, questionnaires, and literature studies. The collected data were then processed and analyzed using quantitative descriptive analysis techniques with IBM SPSS Statistics version 26. Based on the results of the processed data, the research results show that Tcount 4,251 ≥ Ttable 1,675, meaning that there is a significant influence between service quality and patient satisfaction at the Pangkajene Community Health Center, Maritenggae subdistrict, Sidenreng Rappang district. And the influencing factors are 1, Awareness factor with a percentage of 75% in the good category, 2. Regulation factor with a percentage of 82% in the very good category, 3. Ability factor with a percentage of 87% in the very good category, 4. Opinion factor with a percentage of 74% in the good category, 5. Skills and ability factor with a percentage of 75% in the good category, 6. Service facilities factor with a percentage of 82% in the very good category